KESEIMBANGAN UMUM PEREKONOMIAN DALAM PENDEKATAN MATEMATIS - Simatupang, Wandana (STAI Bahriyatul Ulum Pandan, Indonesia, 2024)
Macroeconomic balance (general balance) addresses the market as a whole. In the economy there is a goods market, a money market, and a labor market. Apart from that, there is also the role of government and traders at the export-import level, all of which can influence the general balance. In simple terms, the concept of general equilibrium is a balance of supply and demand. The aim of the research is to find out the national economic balance using various methods including the curve as a supply function. The aim of this finding is how to analyze market balance with national income. Descriptive analysis technique method. The data used is quantitative data using static and mathematical data analysis, namely the regression method of the relationship between independent and dependent variables which is inscribed through graphic data and curves and so on. Results and Conclusions, in general equilibrium briefly provides an explanation of how an economic sector is in equilibrium as evidenced by demand and supply. Various theoretical perspectives such as market theory, law of demand, law of supply, which then establish the relationship between mathematics and supply. Analysis of market balance, which then leads to national income in the form of; consumption, investment, government output and import export studies